Crystallization-driven assembly of fully degradable, natural product-based poly(l-lactide)-block-poly(α-d-glucose carbonate)s in aqueous solution. (28th July 2017) - Song, Yue; Chen, Yingchao; Su, Lu; Li, Richen; Letteri, Rachel A.; Wooley, Karen L.
Abstract: Crystallization-driven self assembly (CDSA) was achieved with fully degradable amphiphilic block polymers derived from three natural products, l -lactide, l -cysteine andd -glucose, to afford spherical and cylindrical nanostructures. A series of functionall -cysteine-modified diblock copolymers, poly(l -lactide)- block -poly(α-d -glucose carbonate)s (PLLA- b -PDGC-cys), was synthesized by organocatalyzed sequential ring-opening polymerization (ROP) ofl -lactide and an alkyne-substituted bicyclic α-d -glucose carbonate, followed by UV-initiated thiol-yne "click" reaction withl -cysteine to render the PDGC block hydrophilic. Incubation of the resulting amphiphilic diblock copolymers in water at 65 °C for 30 h, followed by cooling to room temperature yielded spherical, cylindrical and 2D platelet-like bundled cylinder micellar nanostructures, depending on the PLLA weight percentage in the block copolymer, as revealed by transmission electron microscopy (TEM) and atomic force microscopy (AFM). 1 H NMR spectroscopy was employed to monitor the degradation of the materials over 100 d in aqueous solution at pH 1 and 10 at 37 °C, which allowed for characterization of the stability of the micelles, and for determination of the hydrolytic degradability of the polymer backbone and cleavage of the side chain moieties. Electrospray ionization (ESI) and matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry were used to identify the hydrolytic degradation products of the copolymers. Overall, this work broadens the scope of CDSA to functional, natural-product based degradable block copolymers (BCPs), and the polymeric nanomaterials synthesized in this work hold promise in drug and antimicrobial delivery applications, among others. Graphical abstract: Highlights: Fully natural product-based degradable amphiphilic polymers were synthesized. Spherical, cylindrical and 2D bundled cylindrical micelles were formed. The degradability of these micellar nanoparticles was demonstrated. Crystallization-driven self assembly (CDSA) was broadened to zwitterionic polymers.